Modeling analysis on blood flow into the main artery around knee joint of human leg during sports activities - Norashikin, Nor Tuah (2013)
Vascular injuries are a wide variety of traumatic and nontraumatic injuries to lower limb especially at knee joint. Nowadays, athletes are facing to the vascular injuries that attack to knee joint. The vascular injuries most commonly affect the popliteal artery followed by the common femoral artery through knee joint. The objective of this project is to develop the three dimensional modeling of the knee and investigate the blood flow through human leg. The researcher has been done simulate the model from Fluid Structure Interfaces (FSI) software for blood flow through human leg. In this setup, the values of blood velocity for different gender male and female at range 20-30 years old are been analysis. The different blood velocity during exercise, running and cycling give different result with different gender. Next, normal blood pressure for male and female at 120 mmhg are applied and results were shown the pressure of human after 60 seconds. Besides, variations force are applied to knee joint such as from 250 N, 500 N, 750 N and 1000 N in order to get the result of displacement and stresses on knee joint after impact. Human legs were considering with and without kneepads for analysis the stresses on knee after impact. By using different materials of kneepads such as PVC, ABS, polycarbonate, coconut fiber, oil palm trunk fiber and kenaf fiber the effects of absorption stresses will notice. In three design of artery through knee joint, the 2nd design gives the highest velocity for three conditions during exercise, running and cycling. The blood velocity after 60 seconds during exercise is 75.3 cm/s and 73.3 cm/s, running is 90.1 cm/s and 87.8 cm/s, cycling is 85.1 cm/s and 84.8 cm/s for male and female respectively. Six materials of kneepads are simulated and the kenaf fiber is the most suitable kneepad to protect knee. The stress exerted on kenaf fiber of kneepads is 7.94 MPa at 1000 N for thickness 0.5 cm. After that, the researcher have been applied the kenaf fiber as kneepads for three condition human leg at same angle but different blood flow pattern. The result represent, for 3rd condition human leg give the peak velocity blood flow is 77.13 cm/s and 98.5 cm/s for with and without kneepads. The 3rd condition gives the lowest change rate of displacement, thus the value with and without kneepads are 0.5113 mm and 11.81 mm respectively. In three models of artery with knee joints give three different values of velocity and pressure. Thus, can be prove that, artery for all human are different and doesn’t give the same blood flow velocity through artery. Besides, for three condition of leg shows the different pattern blood flow in human leg for straight, with bones and artery condition.